Efficient narrow-band red-light-emitting diodes based on ambipolar organic single crystals - Gai, Xi; Ye, Gao-Da; Wang, Shi-Rong; Chen, Shuo-Nan; An, Ming-Hui; Wang, Ya-Nan; Ding, Ran; Liu, Yu; Feng, Jing (Organic electronics, 2022)
Organic single crystals have attracted immense attention in the field of organic light-emitting devices (OLEDs), owing to their unique advantages of long-range molecular ordering, high carrier mobility, high fluorescent quantum yield and low impurity content. Development of high-performance organic single crystal-based OLEDs with narrow-band emission is critical for high-purity displaying, yet it is still a major challenge to obtain a crystal-based OLED with both narrow fullwidth at half maximum (FWHM) and high electroluminescence (EL) performance. Here, molecular doping engineering is employed by taking 2,6-diphenylanthracene (DPA) as host crystal and pentacene (Pen) as red guest emitter material. 2,2′-Bis[4-(trifluoromethyl)phenyl]-5,5′-bithiazole (BTPB) with strong electron-withdrawing ability are further doped for the growth of ambipolar crystals in order for balanced hole and electron mobility. As a result, DPA: 3% Pen: 15% BTPB crystal-based OLEDs exhibit a maximum luminance and current efficiency of 10,850 cd m−2 and 1.91 cd A−1, respectively, and an EQE of 1.51%. The obtained red-light-emission with a narrow FWHM increases high color purity of crystal-based OLEDs. It demonstrates that high-performance crystal-based OLEDs with narrow-band emission are of great significance for the development of organic electronics, especially for display and lighting applications. Molecular doping engineering is employed by taking DPA single crystals as host matrix and pentacene as red guest emitter. BTPB with strong electron-withdrawing ability is further doped for obtaining ambipolar crystals. DPA: 3% Pen: 15% BTPB crystal-based OLEDs exhibit a red-light-emission with a narrow FWHM and high-efficiency, which are of great significance for the development of organic single crystal-based electronics. [Display omitted] •Doping of pentacene into host DPA crystal enable narrow-band red-light-emission.•Ambipolar crystals obtained by doping n-type BTPB for balanced charge mobility.•Narrow-band EL emission from crystal-based OLEDs increases a high purity.•DPA: 3% Pe: 15% BTPB crystal-based OLEDs exhibit the highest EL performance.